Copper-Catalyzed Tandem Synthesis of Tetrasubstituted Pyrimidines from Alkynes, Sulfonyl Azides, Trichloroacetonitrile, and Tetramethylguanidine - Yavari, Issa; Nematpour, Manijeh (Synlett, 2013)
The synthesis of a novel class of pyrimidine derivatives via a copper-catalyzed tandem reaction of trichloroacetonitrile, 1,1,3,3-tetramethylguanidine, sulfonyl azides, and terminal alkynes is described.
Keywords: pyrimidine; ketenimines; tandem reaction; sulfonyl azide; terminal alkyne; trichloroacetonitrile; 1,1,3,3-tetramethylguanidine